2007
DOI: 10.1186/1471-2164-8-428
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptional analysis of grapevine berry ripening reveals a set of genes similarly modulated during three seasons and the occurrence of an oxidative burst at vèraison

Abstract: Background: Grapevine (Vitis species) is among the most important fruit crops in terms of cultivated area and economic impact. Despite this relevance, little is known about the transcriptional changes and the regulatory circuits underlying the biochemical and physical changes occurring during berry development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
226
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(259 citation statements)
references
References 92 publications
(115 reference statements)
31
226
1
1
Order By: Relevance
“…Taken together, these data revealed that genes expressed during the immature green phase of development are inhibited after veraison, whereas genes related to sugar accumulation and secondary metabolism are induced. As in the atlas data set, the switch genes appear to regulate the immature-tomature phase transition by the mass downregulation of target genes rather than the activation of new pathways (Lijavetzky et al, 2006;Deluc et al, 2007;Pilati et al, 2007;Lund et al, 2008;Agudelo-Romero et al, 2013).…”
Section: The Grapevine Berry Switch Genes Mainly Encode Transcriptionmentioning
confidence: 99%
“…Taken together, these data revealed that genes expressed during the immature green phase of development are inhibited after veraison, whereas genes related to sugar accumulation and secondary metabolism are induced. As in the atlas data set, the switch genes appear to regulate the immature-tomature phase transition by the mass downregulation of target genes rather than the activation of new pathways (Lijavetzky et al, 2006;Deluc et al, 2007;Pilati et al, 2007;Lund et al, 2008;Agudelo-Romero et al, 2013).…”
Section: The Grapevine Berry Switch Genes Mainly Encode Transcriptionmentioning
confidence: 99%
“…Recent studies have demonstrated that there is a large increase in hydrogen peroxide production postveraison (Pilati et al, 2007), and aquaporins have been shown to facilitate hydrogen peroxide transport across membranes (Bienert et al, 2007). In addition, the ripening process in general is associated with large increases in sugar transport and accumulation, changes in cell wall metabolism, and changes in turgor, all of which are certainly impacted by aquaporins and their modulation of membrane water permeability.…”
Section: Aquaporin Gene Expression and Changes In R Hmentioning
confidence: 99%
“…The respective fruits are themselves named "climacteric." As grapevine is not amongst them, it came somewhat as a surprise when Pilati et al (2007) reported an oxidative burst in cv. "Pinot Noir" that began at veraison and was characterized by rapid accumulation of H 2 O 2 and by the modulation of many ROS scavenging enzymes, previously thought not to be up-regulated in this species.…”
Section: Oxidative Burstmentioning
confidence: 99%
“…Indole-3-acetic acid (IAA) content is high from anthesis to veraison, then declines to very low levels at maturation (Conde et al, 2007). Amidase (AMI1), responsible for the synthesis of IAA from indole-3-acetamide decreases its levels of gene expression during ripening (Pilati et al, 2007), in tandem with the decline of IAA levels.…”
Section: Auxinsmentioning
confidence: 99%